Migration, environmental change and agrarian transition in upland regions: learning from Ethiopia, Kenya and Nepal - Sugden, Fraser; Nigussie, Likimyelesh; Debevec, Liza; Nijbroek, R. (Informa UK Limited, 2022)
This paper analyses the relationship between cyclical labour migration and agrarian transition in the uplands of Nepal, Ethiopia and Kenya. It shows that while migration decision-making is linked to expanding capitalist markets, it is mediated by local cultural, political and ecological changes. In turn, cyclical migration goes on to shape the trajectory of change within agriculture. The dual dependence on both migrant income and agriculture within these upland communities often translates into an intensifying work burden on the land, and rising profits for capitalism. However, on some occasions this income can support increased productivity and accumulation within agriculture – although this depends on both the agro-ecological context and the local agrarian structure.